Study of UV cloud modification factors in Southern Patagonia - Wolfram, Elian Augusto; Orte, Facundo; Salvador, Jacobo Omar; Quiroga, Jonathan Javier; D'elia, Raul Luis; Antón, Manuel; Alados Arboledas, Lucas; Quel, Eduardo Jaime (AIP Conference Proceedings,)
Anthropogenic perturbation of the ozone layer has induced change in the amount of UV radiation that reaches the Earth's surface, mainly through the Antarctic ozone hole, making the ozone and ultraviolet (UV) radiation two important issues in the study of Earth atmosphere in the scientific community. Also the clouds have been identified as the main modulator of UV amount in short time scales and produce the main source of uncertainty in the projection of surface UV level as consequence of projected ozone recovery. While clouds can decrease direct radiation, they can produce an increase in the diffuse component, and as consequence the surface UV radiation may be higher than an equivalent clear sky scenario for several minutes. In particular this situation can be important when low ozone column and partially cloud cover skies happen simultaneously. These situations happen frequently in southern Patagonia, where the CEILAP Lidar Division has established the Atmospheric Observatory of Southern Patagonia, an atmospheric remote sensing site near the city of Río Gallegos (51°55'S, 69°14'W). In this paper, the impact of clouds over the UV radiation is investigated by the use of ground based measurements from the passive remote sensing instruments operating at this site, mainly of broad and moderate narrow band filter radiometers. We analyzed the UV Index obtained from a multiband filter radiometer GUV-541 (UVI) [Biospherical Inc.] installed in the Observatorio Atmosférico de la Patagonia Austral, Río Gallegos, since 2005. Cloud modification factors (CMF, ratio between the measured UV radiation in a cloudy sky and the simulated radiation under cloud-free conditions) are evaluated for the study site. The database used in this work covers the period 2005-2012 for spring and summer seasons, when the ozone hole can affect these subpolar regions. CMF higher than 1 are found during spring and summer time, when lower total ozone columns, higher solar elevations and high cloud cover occur simultaneously, producing extreme ...